Research the Development of Economic Conjuncture - Valkauskas, Romualdas (Ekonomika, 1999)
History the research the development of economic conjuncture is closeness connected with the history of economic statistics practices, with the history of national accounts in Lithuania. System of national accounts is important source to research the development of economical conjuncture.Make of economic indicators is important problem for the research of economic conjuncture. In the research of economic conjuncture often use the list of usual indicators. They may be joining by methods: standardization of data, PATTERN (Planning Assistance Thrum Technical Evaluation of Relevance Numbers) and others.The time series of economic indicators consist trend, seasonal, cyclical and irregular components. To eliminate they components often use procedures which in basis lay methods: moving averages, least-squares. These procedures are ordinary. Anther’s way of identifying the components is to use procedures which in basis lie only the method least-squares. In the article this method explains by using gross domestic product of Lithuania.